Jodoh dan Perjodohan Santri Jamaah Tabligh di Pesantren Temboro - yusuf khummaini; sukron mamun (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam)
This article studies a sociological pesantren community, particularly a  relationship between male and female students in Jamaah Tabligh in Pesantren Temboro. Relationship pattern of male and female students in a pesantren (a traditional Islamic education based on boarding school) tends to be exclusive that inhibits both male and female students to have relationship closely. Interestingly, many students get married at the end of their study. This study investigates how the process on selecting mate, both male and female students, what is the concept of selecting mate (partner) on their perspective, and how the marriage process is practiced by students of Pesantren Temboro. More important is how woman rights on choosing a mate that is determined by their parents. This study is limited field research in Pesantren Temboro, Magetan, East Java as recognized as the largest Islamic education of Jamaah Tabligh in Indonesia. Researchers got the data by interviewing pesantren functionaries related and santri families that did marriage in the pesantren.